LACRIMAL FOSSA MASS - MANAGEMENT DILEMMA - Shoaib, Lt Col Khawaja Khalid (Pakistan Armed Forces Medical Journal, 2010)
Lacrimal fossa mass poses an interesting diagnostic challenge for the ophthalmologist. It usually presents with lid edema, ptosis and globe displacement. Clinician usually expects inflammatory, lymphoproliferative and neoplastic lesions. Patient’s age and durations of symptoms are important considerations. Lymphoproliferative/malignant lacrimal lesions are common in fifth and sixth decades. Pain occurs early in inflammations and late in malignancies1. Orbital echography and CT (computerized tomography) are necessary to know the details. On CT, dacryoadenitis tends to show the gland to be enlarged in an oblong configuration. Neoplastic processes are often more nodular and rounded. Definite diagnosis is given by histopathology in majority of the cases but sometimes it remains doubtful. Role of infectious agents2 and genetic abnormalities3 in the aetiology of ocular adnexal neoplasia are being investigated.